Penanganan Keterlambatan Berbicara (Speech Delay) Dalam Pengaruh Gadget Pada Anak Usia Dini Dengan Metode Bercerita Di Tk Bintang Kecil Tahun Ajaran 2022-2023 - Minarti, Muji -; Muzaqi, Sugito (MOTORIC, 2024)
This research is a qualitative descriptive research that aims to find out and describe how to deal with speech delay using the storytelling method in Bintang Kecil Kindergarten. This study uses a field research method which is descriptive qualitative in nature. The research location was in Bintang Kecil Kindergarten, with the subject of this study involving school principals, parents of children who experienced speech delay, obtained through interviews, observation and documentation. The process of this research illustrates an effort made by a researcher/educator in handling speech delay children, namely by using the storytelling method.